Mammary botryomycosis and hemimastectomy in a post‐partum Welsh Pony mare. (22nd October 2020) - Ciccarelli, M.; Tibary, A.; Ragle, C.
Summary: Botryomycosis is a chronic pyogranulomatous disease characterised by the formation of multiple abscesses containing bacteria surrounded by eosinophilic material which protect them from antibiotics and phagocytosis. Mammary gland botryomycosis is a rare but aggressive disorder that can jeopardise the ability of a mare to nurture a foal. Our report describes a case of unilateral botryomycosis mastitis in a Welsh Pony mare, treated by hemimastectomy. The mare was able to successfully carry and nurse foals post‐surgery.